SEDDS Basic Design and Recent Formulation Advancement: A Concurrent Review - Panigrahi, K.C.; Patra, C.N.; Rao, M.E.B.; Jena, G.K.; Sahoo, L. (Pharmaceutical Nanotechnology, 2022)
In the present scenario, lipid-based novel drug delivery systems are the area of interest for the formulation scientist in order to improve the bioavailability of poorly water-soluble drugs. A selfemulsifying drug delivery system (SEDDS) upon contact with the gastrointestinal fluid, forms an o/w emulsion. SEDDS has gained popularity as a potential platform for improving the bioavailability of the lipophilic drug by overcoming several challenges. The various advantages like improved solubility, bypassing lymphatic transport, and improvement in bioavailability are associated with SMEDDS or SNEDDS. The extent of the formation of stable SEDDS depends on a specific combination of surfactant, co-surfactant, and oil. The present review highlighted the different aspects of formulation design along with optimization and characterization of SEDDS formulation. It also gives a brief description of the various aspects of the excipients used in SEDDS formulation. This review also includes the conflict between types of SEDDS based on droplet size. There is an extensive review of various research regarding different solidification techniques used for SEDDS in the last three years.
Keywords: supersaturation